1998
DOI: 10.1126/science.280.5369.1618
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Alphaherpesviruses Mediated by Poliovirus Receptor-Related Protein 1 and Poliovirus Receptor

Abstract: A human member of the immunoglobulin superfamily was shown to mediate entry of several alphaherpesviruses, including herpes simplex viruses (HSV) 1 and 2, porcine pseudorabies virus (PRV), and bovine herpesvirus 1 (BHV-1). This membrane glycoprotein is poliovirus receptor-related protein 1 (Prr1), designated here as HveC. Incubation of HSV-1 with a secreted form of HveC inhibited subsequent infection of a variety of cell lines, suggesting that HveC interacts directly with the virus. Poliovirus receptor (Pvr) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
820
4
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 847 publications
(846 citation statements)
references
References 18 publications
20
820
4
2
Order By: Relevance
“…For many HSV-1 types, HveA and HveC seem to be the predominant receptor, whereas entry of most HSV-2 involves HveB. 14,16,18 We have previously demonstrated that HSV-2-based recombinant vectors can infect primary human ALL with high efficiency. 3 In accordance with high level expression of all three Hve receptors, we have now extended this observation to HSV-1-derived amplicon vectors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many HSV-1 types, HveA and HveC seem to be the predominant receptor, whereas entry of most HSV-2 involves HveB. 14,16,18 We have previously demonstrated that HSV-2-based recombinant vectors can infect primary human ALL with high efficiency. 3 In accordance with high level expression of all three Hve receptors, we have now extended this observation to HSV-1-derived amplicon vectors.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to primary human cells, we focused our analysis on ALL, the single most common childhood malignancy. The entry of HSV into mammalian cells involves HSV envelope glycoproteins B and/or C. [12][13][14][15] Additional receptors are critical for viral entry into target cells termed herpes virus entry mediators (Hve). HveA is a member of the tumor necrosis factor receptor family, 16,17 whereas HveB and HveC belong to proteins of the immunoglobulin superfamily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 HveA is a member of the TNF receptor family 8 and HveC has been identified as nectin-1a. 7,9 Flow cytometry and indirect immunocytochemistry demonstrated that these receptors were present on the surface of both human preadipocytes and mature adipocytes following differentiation in vitro (Figure 1). By flow cytometry, 2777% of cultured preadipocytes ( Figure 1a) expressed HveA, while 9075% expressed HveC (Figure 1f).…”
Section: Presence Of Hsv Entry Receptors On Adipose Cellsmentioning
confidence: 99%
“…23 To initiate infection, HSV attaches to cell surface glycosaminoglycans such as heparan sulfate and dermatan sulfate, [29][30][31][32][33][34][35] which stabilize the virus such that is can interact with secondary protein receptors required for entry into host cells. [36][37][38] Thus, one possibility to account for the loss of susceptibility to HSV infection is that maturation leads to a decrease in the expression of cell surface molecules required for efficient infection.…”
Section: Introductionmentioning
confidence: 99%